2015
DOI: 10.2169/internalmedicine.54.4853
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Adalimumab for Treating Pyoderma Gangrenosum with Ulcerative Colitis under Corticosteroid-tapering Conditions

Abstract: A 52-year-old woman with ulcerative colitis was admitted to our hospital for an ulcerative colitis flare-up under salazosulfapyridine therapy. The symptoms improved with high-dose corticosteroids. After prednisolone was tapered to 10 mg, the frequency of diarrhea increased. The diarrhea was accompanied by joint pain and a skin ulcer with abscess formation, which was diagnosed to be pyoderma gangrenosum. The patient was started on adalimumab. A positive response to the adalimumab therapy was observed after 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…A total of 3212 unique citations were found. 1286 and 1704 citations were excluded by abstract and full‐text read, respectively, yielding 222 articles…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3212 unique citations were found. 1286 and 1704 citations were excluded by abstract and full‐text read, respectively, yielding 222 articles…”
Section: Resultsmentioning
confidence: 99%
“…Improvement of inflammation around the PNF may suggest improvement of inflammation in the joint-entheseal-nail apparatus. 4,5 In this report, we presented two cases of refractory NP successfully treated with the CPBD gel, and suggest that gel formulation may be superior to ointment formulation in the treatment of NP. Hiroyuki TAKAMA, 1,2 Yoriko ANDO, 1 Takeshi YANAGISHITA, 1 Yuichiro OHSHIMA, 1 Masashi AKIYAMA, 2 Daisuke WATANABE 1 (Fig.…”
mentioning
confidence: 85%
“…The favorable outcome in our case was comparable with the prognosis of TNF-α inhibitor-naïve PG patients who later received ADA within 12 weeks of onset. 1,4 A few PG cases receiving two biologics have been described, mainly switching from IFX to ADA. 1,5 One of these patients received secondary ADA treatment in combination with cyclosporin and prednisolone, and the PG ulcer resolved within 16 weeks.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the studies have suggested the role of biologic therapy, particularly TNF-α (Iinfliximab, adlimumab) and IL-1b inhibitors (canakinumab) in the treatment of PG. Systemic therapy should be complemented by proper pain management and wound care (2,(19)(20)(21)(22).…”
Section: Treatmentmentioning
confidence: 99%